2005
DOI: 10.1002/hbm.20189
|View full text |Cite
|
Sign up to set email alerts
|

Motion standstill leads to activation of inferior parietal lobe

Abstract: Previous studies on motion perception revealed motion-processing brain areas sensitive to changes in luminance and texture (low-level) and changes in salience (high-level). The present functional magnetic resonance imaging (fMRI) study focused on motion standstill. This phenomenon, occurring at fast presentation frequencies of visual moving objects that are perceived as static, has not been previously explored by neuroimaging techniques. Thirteen subjects were investigated while perceiving apparent motion at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…More specifically, the interaural temporal processing of lateralized sounds elicits responses in the contralateral PT, and when the interaural time cue changes in association with a movement, the responses become stronger and extend further into adjacent regions of the IPL [54] . The involvement of IPL in processing of spatial information implies that attention starts to play a role in the task, because it has been confirmed that the multiple-modal IPL is important in processing visual spatial information and orienting visual attention [55,56] . Indeed, when the auditory task requires listeners to selectively compare or evaluate the location of sound source, IPL activity is specifically enhanced [54,57,58] , confirming that the parietal cortex also plays an important role in modulating auditory spatial attention.…”
Section: Discussionmentioning
confidence: 92%
“…More specifically, the interaural temporal processing of lateralized sounds elicits responses in the contralateral PT, and when the interaural time cue changes in association with a movement, the responses become stronger and extend further into adjacent regions of the IPL [54] . The involvement of IPL in processing of spatial information implies that attention starts to play a role in the task, because it has been confirmed that the multiple-modal IPL is important in processing visual spatial information and orienting visual attention [55,56] . Indeed, when the auditory task requires listeners to selectively compare or evaluate the location of sound source, IPL activity is specifically enhanced [54,57,58] , confirming that the parietal cortex also plays an important role in modulating auditory spatial attention.…”
Section: Discussionmentioning
confidence: 92%
“…This area of the brain has been found to be involved in successful change detection and change blindness (Beck et al 2001; Pessoa and Ungerleider 2004;Kim and Blake 2005;Beck et al 2006). Moreover, it is involved in higher order saliencebased as opposed to luminance-based aspects of motion (Battelli et al 2001;Ducommun et al 2002;Sterzer et al 2002;Claeys et al 2003;Federspiel et al 2006;Martinez-Trujillo et al 2006). The momentary activity in this brain area appears to predict the perception of a rotated perspective of a unique stimulus despite the absence of any changes in the physical stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Psychophysical studies have measured the contribution of high-level mechanisms, showing that second-order motion perception is strongly driven by feature tracking (Seiffert & Cavanagh, 1998; 1999; Allen & Derrington, 2000; Ukkonen & Derrington, 2000; Ashida, Seiffert & Osaka, 2001; see Derrington, Allen & Delicato 2004, for review). Regions of the posterior parietal cortex, such as the intraparietal lobule, have been implicated in high-level motion perception (Battelli et al, 2001; Claeys et al, 2003; Federspiel et al, 2006; Ruff, et al, 2008), and it is conceivable that such parietal areas could send feedback signals leading to direction-selective responses in early visual areas. Other candidate brain areas implicated in high-level motion perception include area MT+ as well as the posterior superior temporal sulcus, which has been implicated in biological motion perception (Grossman & Blake, 2001; 2002; Noguchi et al, 2005; Vaina & Dumoulin, 2011).…”
Section: Discussionmentioning
confidence: 99%